EFEITO DO TRATAMENTO TÉRMICO CONVENCIONAL E DO PROCESSO DE EXTRUSÃO SOBRE A QUALIDADE NUTRICIONAL DE ARROZ (Oryza sativa) E FEIJÃO (Phaseolus vulgaris) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Nowadays there are several technological processes that are proving to be efficient in obtaining innovative food products such as extrusion cooking, especially in the processing of starchy raw materials. The objective of this work was to evaluate the effect of conventional heat treatment (cooking in water) and of the extrusion process on the nutritional quality of rice and beans. Three subgroups of rice (polished, parboiled and brown) and two groups of beans (genus Phaseolus and genus Vigna). The proximate composition of raw samples, thermal and viscoamylographic properties of starches were also determined. In the proximal composition, the percentage of dietary fiber ouststands for parboiled brown rice (15%) and the Fradinho bean had the highest protein content (23%). Starch contents were higher in rice (up to 90%) and lower in beans (approximately 50%). The viscoamylographic properties (RVA) of polished rice and Fradinho beans samples showed higher viscosity peak and higher tendency to retrograde, they also showed higher gelatinization enthalpy variation in DSC. In X-ray diffraction from extrused samples were not possible to observe the characteristic type A and C diffraction peaks. In vitro digestibility of starch from samples was analyzed after: cooking in water, frozen-reheated and extruded. It was observed that the rice after cooking in water, frozen-reheated and extruded presented starch available for digestion between 80% and 100%. The beans presented higher percentages of RS to the digestion evaluated at the time of preparation than after freezing and reheating. The bean that presented the highest slowly digestibile starch (SDS) was Carioca in the digestion at the time of preparation (34%) and the Fradinho beans presented the highest level of rapidly digestibile starch (RDS) in the two cooking processes.The different cooking processes have influenced the nutricional quality as well as the recommendation of use according to the consumer´s needs.
Keywords: digestibilidade in vitro; extrusão; grãos cozidos; qualidade nutricional; amido resistente; in vitro digestibility; extrusion; cooked grains; nutritional quality; resistant starch; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS